ATOPIC DERMATITIS: NEW ASPECTS OF TREATMENT - D. Sh. Macharadze ("Paediatrician" Publishers LLC, 2013)
Atopic dermatitis is a chronic inflammatory cutaneous disease, which demands a prolonged treatment. A modern views on the main approaches to treatment of atopic dermatitis in children and adults are analyzed in this article. The treatment is based on the permanent use of emollients in order to achieve an anti-inflammatory effect - topical calcineurin inhibitors (tacrolimus and pimecrolimus), and short courses (5 days) of topical corticosteroids during relapses. For the 10-year period of topical calcineurin inhibitors usage in treatment of atopic dermatitis a great amount of experimental and clinical data have been accumulated. Two the most important changes and additions in the treatment of atopic dermatitis in recent times were related to a new hypothesis of proactive therapy with the use of topical tacrolimus and closing of «black box» warnings, associated to malignization risk due to the long-term usage of topical calcineurin inhibitors. Since atopic dermatitis is characterized by relapsing course, nowadays topical tacrolimus should be considered the most appropriate treatment approach, both in adults and children. The results of investigations confirmed more than 6-times decrease in relapse rate, as well as the significant improvement of quality of life, when the above-mentioned treatment scheme is used, both in children and adults.Key words: children, atopic dermatitis, emollients, treatment, tacrolimus.